Torkildsen's Sport and Leisure Management. - Taylor, Peter (Taylor & Francis, 2010)
This classic textbook provides comprehensive coverage of key topics taught within sport and leisure management courses today. Revised in a new€sixth edition, it provides an insightful and engaging introduction, featuring analysis of managerial ideas and issues required by students aiming for a career in this expanding industry.